Facility
The problem of accumulation and growth of dirt and microorganisms in water use facilities is solved by using members with specific surface layer structures and modified water spray heads in water use facilities, achieving long-term maintenance of surface cleaning.
Patent Information
- Application Number
- JP2023150078
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-15
- Publication Date
- 2025-03-28
AI Technical Summary
In facilities that use water, such as bathrooms, toilets, sinks and kitchens, dirt and microorganisms in the water cause the accumulation and growth of surface dirt, causing unclean and unhealthy odors, and the prior art is difficult to effectively inhibit the adhesion and growth of dirt.
A device is employed that includes a modified water nozzle and a member having a specific surface layer structure. The surface layer structure consists of specific chemicals that inhibit the adhesion and growth of dirt and keep the surface clean by spraying modified water.
Effectively inhibits the adhesion and growth of dirt and microorganisms, keeps the surface clean, and reduces the need for regular cleaning.
Smart Images

Figure 2025042889000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an equipment, and more particularly to an equipment capable of suppressing adhesion or growth of dirt. [Background technology]
[0002] In facilities that use water, such as bathrooms, toilets, washstands, and kitchens, the surfaces of the components that make up the facilities are repeatedly splashed with water containing various types of dirt and dried during use. In such facilities, the dirt contained in the water precipitates on the surfaces of the components, and with repeated use, it accumulates and grows on the surface, becoming visible dirt on the surface and emitting an unpleasant odor. For this reason, it is necessary to remove the dirt by regular cleaning, which is a burden for users.
[0003] The dirt contained in the water that comes into contact with the surface of the components is generated during the use of the equipment, such as washing, defecation, cooking, etc., and includes proteins (skin particles, secretions, hair, excrement, etc.), lipids (derived from sebum, food ingredients, seasonings, etc.), detergent components such as soap, and silicate ions (SiO3 2- ), calcium ion (Ca 2+ ), sulfate ion (SO4 2- ), and compounds that are produced by the reaction of these with each other. When water containing such dirt flows over the surface of a component and is drained away, some of the dirt may remain on the surface. The remaining dirt becomes the starting point for further dirt adhesion, and accumulates and grows on the surface due to interactions between the dirt. Furthermore, in wet environments, microorganisms grow using these dirt as a nutrient source, or these dirt creates an environment suitable for the growth of microorganisms, causing them to grow, and these microorganisms become visible on the surface as unpleasant microbial stains.
[0004] Literature: Koga, Masunaga: Understanding the actual concentration of dirt on the surfaces of bathroom materials and its contribution to fungal growth, Indoor Environment, Vol. 24, No. 1, 2018 (Koga et al., Indoor Environment, Vol. 21, No. 1, pp9-18, 2018) (Non-Patent Document 1) reports that as a result of analyzing dirt on the surfaces of each component that makes up a home bathroom that has been used for a long time, the multiple dirt components mentioned above were detected, and that the composition ratio of keratin protein, triglyceride (sebum component), and sodium fatty acid was high at 90%, and that keratin protein and triglyceride (sebum component) are nutrient sources for the growth of Cladsporium sp., the main mold in bathrooms.
[0005] On the other hand, when such microorganisms grow, their biological action produces sticky organic matter, which combines with the various types of dirt mentioned above and firmly adheres to the surface. This sticky organic matter also becomes a source of residual dirt and promotes the growth of microorganisms. In this way, the dirt and microorganisms contained in the water interact with each other while remaining on the surface of the components and multiplying, so even if the dirt is initially minor, with continued use and the proliferation of microorganisms, it will grow on the surface as strong dirt.
[0006] In order to suppress the proliferation of microorganisms in facilities that use water, such as bathrooms, toilets, washstands, kitchens, etc., it has been proposed to discharge water that has been modified to suppress the proliferation of microorganisms. JP-A-9-220273 (Patent Document 1) discloses a method and device for spraying free chlorine-containing water, which is generated by electrolyzing chlorine ion-containing water, onto the walls and floor of a bathroom in order to prevent the walls and floor of the bathroom from becoming dirty due to bacteria.
[0007] On the other hand, in the chemical antibacterial technology such as the above-mentioned free chlorine-containing water, the presence of organic matter may reduce the original ability (antibacterial power) of the active ingredient (free chlorine). For example, it is known that the antibacterial effect of free chlorine-containing water and ozone water is weakened by binding with organic components. In addition, when the surface of a component is covered with dirt components, or when it is difficult or impossible for the active ingredient to directly contact the surface of the component, microbial contamination may occur between the dirt and the surface of the component.
[0008] Therefore, in order to prevent the occurrence of microbial contamination on the surface of a component, that is, to inhibit the proliferation of microorganisms, it is essential that the active ingredient is brought into direct contact with the surface of the component.
[0009] To solve this problem, Japanese Patent Laid-Open Publication No. 2019-092841 (Patent Document 2) discloses a bathroom that makes it easy to bring electrolyzed water into contact with the surface of the washing area floor hidden by sebum stains. According to Patent Document 2, by landing electrolyzed water at a landing angle of 0° to 16° with respect to the horizontal direction of the washing area floor surface, which is hydrophilic and has a certain degree of oil repellency, the electrolyzed water can be allowed to penetrate between the sebum stains and the floor surface, so that the effect of electrolyzed water can be effectively exerted in a bathroom environment where sebum stains adhere.
[0010] Furthermore, techniques have been proposed for modifying the surface of components in order to suppress adhesion of dirt to the surface of the components and to improve the ease of cleaning the adhered dirt.
[0011] For example, JP 2008-239949 A (Patent Document 3) discloses a hydrophilic member having a surface excellent in antifouling property, antifogging property and abrasion resistance. Specifically, the member discloses a hydrophilic film formed on a substrate by bonding a zwitterionic low molecular weight compound having a betaine structure to a hydrophilic polymer having a silane coupling group at the end or side chain by silane coupling, and introducing inorganic components such as Si, Ti, Zr, and Al for densification.
[0012] In addition, WO2018 / 079592 (Patent Document 4) discloses a laminate sheet having a substrate layer and a hydrophilic coating layer formed using a resin composition containing an aqueous polyester resin and a zwitterionic polymer. This laminate sheet is said to be resistant to fogging and has excellent antifouling properties.
[0013] In addition, WO2018 / 155577 (Patent Document 5) discloses a hydrophilic structure having a layer structure in which a substrate, an intermediate layer, and a hydrophilic layer are laminated in this order, the intermediate layer being a layer containing a siloxane-based polymer, and the hydrophilic layer containing a zwitterionic polymer having no silicon atoms. This structure is said to have excellent hydrophilicity, contamination resistance, adhesion, and water resistance. [Prior art documents] [Patent documents]
[0014] [Patent Document 1] Japanese Patent Application Publication No. 9-220273 [Patent Document 2] JP 2019-092841 A [Patent Document 3] JP 2008-239949 A [Patent Document 4] WO2018 / 079592 publication [Patent Document 5] WO2018 / 155577 publication [Non-patent literature]
[0015] [Non-Patent Document 1] Koga, Masunaga: Understanding the actual state of dirt concentration on bathroom material surfaces and its contribution to fungal growth, Indoor Environment, Vol. 24, No. 1, 2018 (Koga et al., Indoor Environment, Vol. 21, No. 1, pp9-18, 2018) Summary of the Invention [Problem to be solved by the invention]
[0016] The inventors focused on the fact that various components (proteins, lipids, detergent components such as soap, ionic components contained in the water used, compounds produced by reactions between these, etc.) adhere to the surfaces of components that make up water-using facilities such as bathrooms, toilets, washbasins, and kitchens when the facility is used.
[0017] In general, in a member used in an environment where water is splashed, by making the surface a hydrophilic surface, the affinity with hydrophobic dirt is reduced, and when water is splashed, the water spreads over the surface, which has the advantage of floating and making it easier to remove the attached hydrophobic dirt. In order to make the surface of the member hydrophilic, it is common to impart polar groups to the surface. By providing the polar groups, the affinity with anions increases if the polar groups are cationic groups, and the affinity with cations increases if the polar groups are anionic groups. Some of these ionic dirt particles are adsorbed to the surface, which may become the starting point for the growth of dirt. For example, there is a risk of electrostatic adsorption of silicate ions to cationic groups and calcium ions to anionic groups. When the adhesion density of electrostatically adsorbed silicate ions increases, polymerization due to dehydration condensation between silicate ions is induced or promoted, and when the adhesion density of silicate ions increases further in this state, the generated polymer becomes denser, which may cover the surface of the member as water stains. In addition, calcium ions react with CO2 in the air or water, and as the water evaporates, they densely crystallize as calcium carbonate, which adheres to the surface of the component, either alone or as a mixture, to form limescale. Furthermore, when a large amount of water adheres to the surface of the component, or when water adheres to the surface of the component and dries repeatedly, the amount and frequency of silicate ions and calcium ions adhere to the surface of the component increases, accelerating the formation of limescale and resulting in a state in which limescale adheres strongly to the surface of the component, i.e., the limescale is fixed to the surface of the component.
[0018] In addition, since proteins have hydrophobic regions, positively charged regions, and negatively charged regions in their molecules, they are adsorbed to polar groups present on both hydrophobic and hydrophilic surfaces due to hydrophobic and electrostatic interactions.
[0019] If any of these stains remain on the surface of the component, various other stains may be adsorbed and accumulated from the stain. Furthermore, as mentioned above, microorganisms may grow using these stains as a nutrient source, or these stains may become a favorable environment for the growth of microorganisms, causing the microorganisms to grow and become visible on the surface as unpleasant microbial stains. Alternatively, when the microorganisms grow, they may produce sticky organic matter through biological action, which may combine with the various stains mentioned above and firmly adhere to the surface, and this sticky organic matter may become a starting point for the remaining of further stains.
[0020] In this way, the dirt and microorganisms contained in the water remain on the surface of the components and grow and accumulate while interacting with each other, so even if the dirt is initially minor, with continued use and the proliferation of microorganisms, it will grow into strong dirt on the surface.
[0021] Therefore, in order to inhibit the adhesion or growth of dirt on the surface of a component exposed to water containing such various types of dirt, it is desirable for the surface to be hydrophilic and have a low affinity for proteins, and further for the surface to inhibit the adsorption of ionic components and the growth of microorganisms to be inhibited.
[0022] The present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide equipment that can suppress the adhesion of dirt to the surface of a component or the growth of dirt on the surface of a component, thereby making it possible to maintain the surface of the component in a clean state for a long period of time. [Means for solving the problem]
[0023] According to the invention described in claim 1, which has been made to achieve the above object, a mechanism for discharging reformed water obtained by reforming tap water and a member having a surface onto which the reformed water is sprayed are provided, and the member has a compound represented by the following formula (A1): [ka] The surface layer has a sliding durability and includes a structure represented by the formula: In formula (A1), L1 is -COO-, -CONH-, -(CH2) m - (where m is a natural number), R1 is H or CH3; X1 is a functional group represented by the following formula (B1) or the following formula (B2), [ka] [ka] In formula (B1), R3 and R6 each independently represent -(CH2) l - (l is a natural number from 1 to 10), R4 and R5 are each independently a group containing C and H as essential components and O as an optional component, but not containing N or S; In formula (B2), R7 and R8 each independently represent -(CH2) l - (l is a natural number from 1 to 10), R9, R 10 , R 11 are each independently a group containing C and H as essential components and O as an optional component, and not containing N or S. This feature makes it possible to suppress the adhesion of dirt to the surface of a component and the growth of dirt on the surface of a component starting from the adhered dirt, thereby making it possible to keep the surface of the component clean for a long period of time without performing special cleaning procedures.
[0024] According to the invention described in claim 2, by suppressing the concentration of anionic groups, cationic groups, and the concentration of Si atoms that are firmly bonded to the silicate ions contained in tap water on the surface of the surface layer of the component, it is possible to suppress the adsorption of silicate ions and the formation of limescale stains.
[0025] According to the invention described in claim 3, by making the static contact angle of water with respect to the surface of the surface layer of the member 35° or less, it is possible to suppress adhesion of hydrophobic dirt to the surface.
[0026] According to the invention described in claim 4, by using the modified water as sterilizing water, it is possible to inhibit the growth of dirt caused mainly by the proliferation of microorganisms on the surface, or by using the modified water as deionized water, it is possible to inhibit the formation of limescale on the surface and inhibit the growth of dirt and limescale that originates from these.
[0027] According to the invention as recited in claim 5, by using electrolytic water obtained by electrolyzing tap water as the reformed water, it is possible to produce the reformed water without adding any chemicals or the like.
[0028] According to the invention described in claim 6, the mechanism for discharging the modified water includes an ejection section for ejecting the modified water and a device for generating electrolytic water, so that electrolytic water, which has a short half-life, can be ejected immediately after it is generated, making it possible to efficiently act on the surface of the component and, ultimately, on dirt on the surface of the component. Effect of the Invention
[0029] According to the present invention, it is possible to provide equipment capable of suppressing adhesion of dirt to a surface of a component and growth of dirt on the surface of the component. [Brief description of the drawings]
[0030] [Figure 1] FIG. 1 is a schematic diagram of an example of an installation according to the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view of an example of a member according to the present invention. [Diagram 3] FIG. 1 is a schematic diagram of an example of an electrolysis device according to the present invention. [Figure 4] FIG. 1 is a schematic diagram of an example of an electrolysis device according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] 1.Equipment The equipment according to the present invention includes a mechanism for discharging reformed water obtained by reforming tap water, and a member having a surface onto which the reformed water is applied. The member includes a surface layer having sliding durability, which includes a structure represented by formula (A1) on a part or all of its surface. Fig. 1 is a schematic diagram of an example of equipment according to the present invention. In the embodiment shown in Fig. 1, the equipment according to the present invention includes a reformed water generating device 2 and a member 4, and tap water supplied from a water conveying section 1 is reformed in the reformed water generating device 2 and then discharged from a reformed water discharge section 3 to the member 4. In the embodiment shown in Fig. 1, the mechanism for discharging the reformed water includes the reformed water generating device 2 and the discharge section 3.
[0032] Specific examples of wet spaces in which the equipment according to the present invention is preferably used, or specific examples of the equipment itself according to the present invention, include toilets, hand washing basins, washstands, vanity units, system kitchens, bathrooms, etc. These wet spaces or equipment are used in environments where water containing various types of dirt splashes on their surfaces, or where water dries with water and dirt mixed on the surface, and it is well known that the attached contaminants become stuck and become difficult to clean, or that microorganisms grow using the contaminants as food or habitat, resulting in a situation where the contamination can be seen with the naked eye, or that unpleasant phenomena due to microbial contamination occur, such as the generation of foul odors.
[0033] 2. Materials 2-1. Use of materials The members in the present invention are elements that constitute the facility. Specific examples of components include, for example, in the case where the facility is a bathroom, floors, walls, ceilings, doors, counters, racks, bathtubs, aprons, bathtub covers, drains, mirrors, and parts associated with these. In the case where the facility is a toilet, components include floors, toilet bowls, tanks, toilet lids, toilet seats, heated toilet seats, and parts associated with these. In the case where the facility is a washroom, components include washbasins, washbasin counters, faucets, drains, and parts associated with these. In the case where the facility is a kitchen, components include sinks, counters, faucets, drains, dishwashers, and parts associated with these.
[0034] 2-2.Component composition The member of the present invention has a surface layer on a part or the whole of its surface. FIG. 2 is a schematic cross-sectional view of an example of a member having a surface layer on the whole of its surface. In the embodiment shown in FIG. 2, the member 10 has a base material 11 and a surface layer 12. The surface layer 12 is preferably on the outermost surface of the member 10. In this case, the surface of the surface layer 12 is the surface of the member 10. The member 10 may further have an intermediate layer 13 and / or a primer layer 14 described later. The member 10 may further have layers (not shown) other than the above as long as the effects of the present invention can be achieved. The fact that the member 10 has the surface layer 12 can be confirmed by observing the cross section of the member 10 using an electron microscope and separating the layers.
[0035] 2-2-1. Base material In the present invention, the substrate is not particularly limited. As the material of the substrate, any material generally used for a portion exposed to water, such as resin, metal, inorganic material (glass, ceramic, etc.), can be used. In addition, the shape of the substrate is not particularly limited. For example, it may be a flat plate or may have a complex shape.
[0036] 2-2-2.Surface layer In the present invention, the surface layer of the member contains a structure represented by the following formula (A1). [ka] In formula (A1), L1 is -COO-, -CONH-, -(CH2) m - (where m is a natural number), R1 is H or CH3; X1 is a functional group represented by the following formula (B1) or the following formula (B2), [ka] [ka] In formula (B1), R3 and R6 each independently represent -(CH2) l - (l is a natural number from 1 to 10), R4 and R5 are each independently a group containing C and H as essential components and O as an optional component, but not containing N or S; In formula (B2), R7 and R8 each independently represent -(CH2) l - (l is a natural number from 1 to 10), R9, R 10 , R 11 are each independently a group containing C and H as essential components and O as an optional component, and containing neither N nor S.
[0037] In the present invention, the surface layer of the member has a sliding durability. The member of the present invention is maintained by rubbing the member with a sponge, cloth, or the like soaked in water and a detergent containing water. The surface layer of the present invention has the following sliding durability, and can maintain the effect of suppressing the adhesion or growth of dirt for a long period of time even in the above-mentioned environment.
[0038] <Sliding durability evaluation> The sliding durability of the surface layer in the present invention can be evaluated by carrying out a sliding durability test using a sliding machine (manufactured by Tester Sangyo Co., Ltd.) according to the following method. A commercially available urethane sponge (Scotch-Brite Bath Shine, manufactured by 3M Japan Co., Ltd.) was soaked in a mixture of water and neutral detergent (Bath Magiclean, manufactured by Kao Corporation) in a weight ratio of 90:10, and subjected to a load of 25 [g / cm 2 The surface of the surface layer is then washed with running water, dried, and the surface is then subjected to X-ray photoelectron spectroscopy (XPS) to obtain the N + N atoms belonging to (hereinafter referred to as "N + The concentration of the ions (referred to as "atoms"), the concentration of S atoms, and the concentration of P atoms can be measured and judged as follows: Good sliding durability: N on the surface after sliding + The concentration of N atoms, S atoms, and P atoms on the surface before sliding + The concentration of the atoms, the concentration of the S atoms, and the concentration of the P atoms are 60% or more. Insufficient sliding durability: N of the surface after sliding + The concentration of N atoms, S atoms, and P atoms on the surface before sliding + The concentration of the atoms, the concentration of the S atoms, and the concentration of the P atoms are less than 60%.
[0039] In the present invention, the surface layer of the member is a N + It is preferable that the concentration of S atoms is 0.3% or more and 2.8% or less, and the concentration of S atoms, the concentration of P atoms, or the sum of the concentrations of S atoms and P atoms is 0.3% or more. A specific measurement method will be described later, but these characteristics mean that control of the content of cationic groups and anionic groups contained in the surface layer is important for achieving the above-mentioned effects of the present invention, and by controlling it within this range, an effect of achieving both inhibition of protein adhesion and inhibition of limescale adhesion can be obtained.
[0040] Furthermore, it is preferable that the surface layer of the component does not contain more than a specified amount of Si atoms, which are prone to adhesion of water scale, and it is preferable that the concentration of Si atoms obtained by measuring the surface by X-ray photoelectron spectroscopy (XPS) is 1.0% or less.
[0041] By including a structure represented by formula (A1) in the surface layer, the member of the present invention can reduce the adsorption force of various contaminants to the surface of the surface layer. In particular, it is possible to reduce the adhesion force of proteins. That is, the surface of the member of the present invention can suppress the adhesion of various contaminants, particularly proteins, and can suppress the growth of dirt originating from contaminants.
[0042] The mechanism of this inhibition is considered as follows, but it is merely a hypothesis, and the present invention is not limited by this hypothesis. The structure represented by formula (A1) is a betaine structure as described later, and has antifouling ability (ability to inhibit protein adsorption). This performance can inhibit protein adhesion to the surface of a component. This prevents the adhesion of protein stains to the surface of the component and the growth of stains originating from this, and further inhibits the adhesion of proteins that serve as food for microorganisms such as mold, thereby inhibiting the growth of microbial stains. In addition, when sterilized water is used as modified water described later, the inhibition of protein stains on the surface of the component prevents the weakening of the effect of the sterilized water, and the generation of microbial stains can be more effectively inhibited. On the other hand, N in the structure represented by formula (A1) +There is a risk that silicate ions will be electrostatically adsorbed to the site. In this case, the amount of silicate ions attached will increase. In other words, the attachment density of silicate ions will increase. This will induce or promote polymerization by dehydration condensation between silicate ions, and if the attachment density of silicate ions increases further in this state, the generated polymer will become denser, which may cover the surface of the component as scale. If the surface of the component is covered with scale to a certain extent or more, the protein adhesion suppression effect will be hindered, and the protein removal effect by applying modified water to the surface of the component with a weak water landing pressure, as described below, may also be reduced. When there is a concern about the adsorption of silicate ions, it is more preferable to control the content of the structure represented by formula (A1) contained in the surface layer of the component of the present invention. By controlling the content of the structure represented by formula (A1), N + By preventing the amount of sites from becoming too large and controlling the amount of components such as Si to which silicate ions are likely to adhere, the adhesion density of the silicate ions can be kept low, and polymerization of the silicate ions and densification of the resulting polymer can be suppressed.
[0043] In a more preferred embodiment of the member of the present invention, the surface layer contains a structure represented by formula (A1) and further contains other organic components (preferably, both are present randomly). By containing an organic component other than the structure represented by formula (A1), the N contained in the surface layer can be + The amount of sites can be controlled, thereby blocking the polymerization of silicate ions and the densification of the resulting polymer, making it possible to inhibit the adhesion of limescale and effectively inhibiting the adhesion of protein.
[0044] In a preferred embodiment of the modified water of the present invention, by using deionized water, the cationic N + Adsorption of anionic silicate ions to the site and / or anionic SO3 - Site, PO4 -It is possible to suppress the adsorption of cationic calcium ions to the surface of the component. By reducing the amount of ionic components adhering to the surface of the component, it is possible to suppress the adhesion of ionic components and the growth of dirt that originates from these ionic components.
[0045] In the present invention, the surface layer containing a structure represented by formula (A1) means that the surface layer contains one or more types of structures represented by formula (A1).
[0046] In the present invention, the surface layer is preferably a polymer layer. The polymer layer is a layer containing a polymer compound. In the present invention, the surface layer preferably contains a polymer compound containing a structure represented by formula (A1), and in the surface layer, the structure represented by formula (A1) and the structure containing any other organic component are preferably randomly bonded. That is, the surface layer preferably contains a random copolymer of the structure represented by formula (A1) and a structure containing an organic component other than the structure represented by formula (A1). The state in which these structures are randomly bonded can be determined by observing the surface to see that the structure represented by formula (A1) is not locally unevenly distributed.
[0047] The surface layer contains a random copolymer. 13 It is possible to confirm this by using C-NMR to qualitatively characterize the copolymer species and quantitatively analyze the monomer sequence fraction (mol), monomer composition ratio (mol%, wt%), etc. For example, when the structure represented by formula (A1) is Z and the structure containing an organic component other than the structure represented by formula (A1) is S, if a ZSZ or SZS sequence is present, the surface layer contains a random copolymer.
[0048] The structure represented by formula (A1) and the structure containing an organic component other than the structure represented by formula (A1) will be further explained.
[0049] 2-2-2-1. Structure represented by formula (A1) In formula (A1), L1 is preferably -COO-. This can further suppress protein adhesion and water stain adhesion. When L1 is -CONH-, protein adhesion or water stain adhesion may occur starting from the N that constitutes -CONH-. Also, when L1 is -(CH2) m If the value is -, the hydrophobicity increases and protein adhesion may occur.
[0050] In the structure represented by formula (A1), X1 is preferably a functional group represented by formula (B1). This can further suppress the adhesion of proteins and the fixation of limescale. Even if X1 is a functional group represented by formula (B2), it is effective, but since the sulfonic acid group contained in formula (B1) exists as a resonance hybrid due to the delocalization of the unpaired electron and is very stable, it is assumed that it has low reactivity with contaminants such as silicate ions and proteins, and therefore has a higher effect.
[0051] In X1 of formula (A1), that is, in formula (B1) or formula (B2), l of R3, R6, R7, and R8 is preferably 1 to 6, more preferably 1 to 5, and even more preferably 1 to 3. This allows cationic N + Adsorption of anionic silicate ions and / or anionic SO3 - Site or PO4 - The adsorption of cationic calcium ions to the site can be minimized. This allows the structure represented by formula (A1) to form a stable molecule. That is, the cationic N + The anionic SO3 site at the end of the structure represented by formula (A1) - PO4 in the site or formula (A1) - Since the distance from the site is not too large, the anionic silicate ions and / or cationic calcium ions are prevented from easily approaching the structure represented by formula (A1) (i.e., the surface layer), and the adsorption of the anionic silicate ions and / or cationic calcium ions can be suppressed.
[0052] 2-2-2-2. Structure containing organic components other than the structure represented by formula (A1) The structure containing an organic component other than the structure represented by formula (A1) is preferably represented by the following formula (A2). [ka] In formula (A2), L2 is -COO-, -CONH-, -(CH2) m -(m is a natural number), -Ph- (phenyl group), R2 is H or CH3; X2 preferably contains any structure selected from the group consisting of the following formula (C), the following formula (F1), the following formula (F2), the following formula (G), and the following formula (H). [ka] In formula (C), Y is a linear, branched or cyclic hydrocarbon group having 1 to 10 carbon atoms; a is a natural number, R 12 includes any structure selected from the group consisting of H, CH3, C2H5, and the following formula (D1), the following formula (D2), the following formula (D3), and the following formula (D4). [ka] [ka] [ka] [ka]
[0053] In formula (D1), Y is a linear, branched or cyclic hydrocarbon group having 1 to 10 carbon atoms; L3 is -OCO-, -NHCO-, -(CH2) m- (where m is a natural number), R2 is H or CH3.
[0054] In formula (D2), Y is a linear, branched or cyclic hydrocarbon group having 1 to 10 carbon atoms; X3 is a structure represented by the following formula (E1). [ka] In formula (E1), Y is a linear, branched or cyclic hydrocarbon group having 1 to 10 carbon atoms; L3 is -OCO-, -NHCO-, -(CH2) m - (where m is a natural number), R2 is H or CH3; a is a natural number.
[0055] In formula (D3), Y is a linear, branched or cyclic hydrocarbon group having 1 to 10 carbon atoms; X3 is a structure represented by the above formula (E1).
[0056] In formula (D4), X4 is a structure represented by the following formula (E2). [ka] In formula (E2), Y is a linear, branched or cyclic hydrocarbon group having 1 to 10 carbon atoms; L3 is -OCO-, -NHCO-, -(CH2) m - (where m is a natural number), R2 is H or CH3; a is a natural number.
[0057] [ka] [ka] In formula (F2), R 13 is a group which contains C and H as essential components, O as an optional component, and which does not contain N or S. [ka] In formula (G), R 14 is -(CH2) l - (l is a natural number from 1 to 10), R 15 , R 16 , R 17 are each independently a group containing C and H as essential components and O as an optional component, and containing neither N nor S.
[0058] [ka] In formula (H), R 18 is a straight-chain, branched-chain, or cyclic hydrocarbon group having 1 to 10 carbon atoms.
[0059] The structure containing an organic component other than the structure represented by formula (A1) does not itself actively act on contaminants, but its main role is to dilute the concentration of the betaine structure in the surface layer. Among them, a (meth)acrylic structure is preferable, and a hydrophilic structure is even more preferable. Specifically, as a characteristic of the surface layer, it is more preferable that the static contact angle of water with the surface of the surface layer is 35° or less. The (meth)acrylic structure increases the compatibility with the structure represented by formula (1) and makes it easier to copolymerize randomly, and the hydrophilicity does not impair the effect on hydrophobic dirt and proteins containing a large amount of hydrophobic organic components. This can improve the effect of suppressing the adhesion of organic components such as proteins.
[0060] In addition, as a resin component that is commonly used as an organic component of a structure containing an organic component other than the structure represented by formula (A1), a polyester-based structure as represented by the following formula (N) can be mentioned, but it is preferable that the present invention does not contain this structure. As a non-limiting reason, it is presumed that the polyester-based resin component contains many O atoms, which become adsorption points for silicate ions and easily form water scale. In the present invention, it is preferable that the O atom concentration obtained by XPS is 40% or less, and within this range, the desired effect can be exhibited without any problems. [ka]
[0061] In the present invention, whether the surface layer contains the structure represented by formula (A1) can be specified by any one of the following methods or a combination of multiple methods.
[0062] <Infrared spectroscopy (IR)> By measuring the infrared light absorption spectrum near the surface of the surface layer using infrared spectroscopy, the functional groups contained in the surface layer can be estimated. For example, it is possible to identify the presence of -C=O and -CO- in an ester bond (-COO-) from the absorption wavenumber. Methods for measuring the infrared absorption spectrum near the surface of the surface layer include a method in which the surface layer is scraped off and collected, and the powder is measured using a transmission method, and more convenient methods include a single reflection ATR method and a microscopic ATR method.
[0063] <Time-of-flight secondary ion mass spectrometry (TOF-SIMS)> TOF-SIMS can obtain the structural information of the organic substances present on the surface of the surface layer. By evaluating the surface layer with TOF-SIMS, it is possible to identify the substructure from the fragment peaks specific to the structure represented by the formula (A1). For example, when the structure represented by the formula (A1) is the structure represented by the following formula (A1-1), fragment peaks specific to m / z = 279.11 and m / z = 421.26 can be detected. When measuring with TOF-SIMS, in order to remove the dirt on the surface of the sample to be measured, as a pretreatment, the surface of the sample is sputtered by several nanometers with an ion source such as a gas cluster ion beam (GCIB), and then Bi3 2+ and other primary ion sources are irradiated, and the fragments are measured.
Chemical formula
[0064] <X-ray photoelectron spectroscopy (XPS)> By XPS, it is possible to identify the composition ratio and chemical bond state of C, N, O, and S contained in the molecules constituting the surface layer. For example, the XPS spectrum (N1s orbital) of N atoms derived from a sulfobetaine structure as shown in formula (A1-1) has a peak position at a binding energy of 401.5 eV when no other ionic mixtures are present. In contrast, when the structure represented by formula (A1) is a structure as shown in the following formula (A3) (a structure containing a cationic ammonium moiety) or a mixture of formula (A3) and the following formula (A4) (a structure containing an anionic sulfonic acid moiety), the peak positions are 402.0 eV and 401.8 eV, respectively. In this way, it is possible to identify whether or not an N atom is derived from sulfobetaine based on the difference in peak position. Similarly, it is possible to identify whether S atoms are derived from sulfobetaine from the peak position. The XPS spectrum (S2p orbital) of S atoms derived from the structure shown in formula (A1-1) has a peak position at a binding energy of 166.2 eV, whereas the peak positions are 167.5 eV and 167.1 eV for the structure shown in formula (A4) (anionic sulfonic acid) or a mixture of formulas (A3) and (A4). All of these peak positions are obtained by correcting with the peak position of the C1s orbital at 284.5 eV. [ka] [ka]
[0065] <Nuclear magnetic resonance measurement (NMR)> NMR can provide information on the bonding state of H, C, and N contained in the molecules that make up the surface layer and their interactions with neighboring atoms through chemical shifts compared with standard samples, allowing the molecular structure that makes up the surface layer to be identified in detail.
[0066] 2-2-3.Static contact angle of surface layer In the present invention, the static contact angle of water with the surface of the surface layer is preferably as low as possible. Specifically, it is preferably 35° or less, more preferably 30° or less, and even more preferably 20° or less. This increases hydrophilicity, making it possible to suppress adhesion of various contaminants including proteins and the growth of dirt originating from the adhered contaminants, thereby making it possible to maintain the surface of the component in a clean state for a long period of time.
[0067] <Measurement of static contact angle of water on a surface> The static contact angle of water with respect to the surface of the surface layer is measured, for example, using the following device and software under the following measurement conditions. Equipment: DMo-702 (Kyowa Interface Science Co., Ltd.) Software: FAMAS integrated interface measurement / analysis system Version:7.3.0 Measurement method: Droplet method Droplet volume: 2.0μL Waiting time: 1000ms Analysis method: θ / 2 method
[0068] 2-2-4. Ratio of the structure represented by formula (A1) (betaine structure) in the surface layer In the present invention, the content of the structure represented by formula (A1) (betaine structure) in the surface layer is determined by the N + N atoms (N + In the present invention, the concentration of N obtained by XPS measurement of the surface of the member can be specified. + The concentration of the atoms is preferably 0.3% or more and 2.8% or less, and more preferably 0.4% or more and 2.6% or less.
[0069] When the surface layer contains a structure represented by formula (H), the N + The concentration of atoms is N from the structure represented by formula (A1). + The concentration of atoms and N from the structure represented by formula (H) +The total concentration of atoms is obtained. In such a case, the proportion of the structure (betaine structure) represented by the formula (A1) can be defined by the concentration of S atoms, the concentration of P atoms, or the total of the concentration of S atoms and the concentration of P atoms.
[0070] In the present invention, the concentration of S atoms, the concentration of P atoms, or the total of the concentration of S atoms and the concentration of P atoms obtained by subjecting the surface of the member to XPS measurement is preferably 0.3% or more, and more preferably 0.5% or more.
[0071] In the present invention, the concentration of Si atoms obtained by subjecting the surface of the member to XPS measurement is preferably 1.0% or less, and more preferably 0.7% or less. Since the concentration of Si atoms contained in the surface of the member is low, adsorption of silicate ions and formation of scale can be suppressed.
[0072] <XPS measurement> · Preparation of measurement sample A measurement sample can be a flat plate-shaped region cut from a member sample with an appropriate size. It is preferable to clean the surface of the measurement sample before measurement. For example, the surface of the measurement sample can be cleaned using a neutral detergent and a sponge, and then thoroughly rinsed with ultrapure water. · XPS measurement device For the XPS measurement device, K-alpha (manufactured by ThermoFisher Scientific Co., Ltd.) can be used. · XPS measurement conditions X-ray conditions: Monochromatized AlKα ray, 72W - 12KV Photoelectron extraction angle: 90° Analysis area: 400μmφ Neutralization gun conditions: 200μA Ion gun conditions: 10mA (Survey) Time per step: 10ms Energy step size: 1.000eV Sweep: 2 times Pass energy: 200eV Scanning range: -10~1350 eV (Narrow) Time per step: 50 ms Energy step size: 0.100 eV Sweep: 5 times Pass energy: 50 eV Scanning range: C1s peak 279.000 eV~298.000 eV, O1s peak 525.000 eV~545.000 eV, N1s peak 392.000 eV~410.000 eV, S2p peak 157.000 eV~175.000 eV, Si2p peak 95.000 eV~110.000 eV, P2p peak 124.000 eV~144.000 eV
[0073] <Calculation of atomic concentrations of each atom (S, N, Si, P)> The atomic concentrations of the detected elements can be calculated from the obtained spectra using, for example, data analysis software Thermo Avantage (version 5.9916, manufactured by Thermo Fisher Scientific Co., Ltd.). First, use the spectrum obtained from the survey analysis to confirm whether the cleaning has been properly performed. Next, perform charge correction on the spectrum obtained from the narrow analysis with the C1s peak set to 284.5 eV. Then, after removing the background by the Smart method for the peaks based on the electron orbits of each measured atom, calculate the peak area intensity and perform an analysis process of dividing by the sensitivity coefficient specific to the device preset in the data analysis software to calculate the atomic concentrations of C atoms, O atoms, N atoms, S atoms, Si atoms, and P atoms when the total of these atoms is 100%.
[0074] <Peak separation of N atoms> To separate the peak derived from the +1 valence N atom (N + ) contained in the betaine structure from the peak derived from other 0 valence N atoms (N 0 ), the following method can be used. Fix the peak position of N + at 401.4~401.8 eV and the full width at half maximum of the peak at 1.6 eV, and for N 0The peak position of N is fixed at 398.7 to 399.4 eV and peak fitting is performed. + , N 0 The atomic concentration of each is calculated.
[0075] In the present invention, the surface layer may be provided on the substrate. The surface layer may be provided on the surface of the substrate. In other words, the surface layer may be formed directly on the surface of the substrate without including any other layer between the substrate and the surface layer. When the surface layer is provided on the surface of the substrate, the surface layer is preferably a gradient film with a gradient composition. Specifically, the surface side of the surface layer preferably includes a structure represented by formula (A1), and the substrate side of the surface layer preferably includes a gradient film whose main chain contains a large amount of acrylic resin or polyvinyl resin, as described later. This makes it possible to ensure close contact with the substrate while suppressing the adsorption of proteins and the formation or adsorption of water scale.
[0076] 2-2-5. Composition for forming surface layer In the present invention, the surface layer is preferably a cured surface layer forming composition. In the present invention, the surface layer forming composition may contain a compound having a betaine structure, a polymerization initiator, and a solvent. More preferably, the surface layer forming composition further contains a polymerizable organic compound other than betaine.
[0077] 2-2-5-1. Compounds with betaine structure In the present invention, the composition for forming a surface layer can contain a compound having a betaine structure. This allows the surface layer obtained by curing the composition for forming a surface layer to contain a structure represented by formula (A1). In the present invention, a compound having a betaine structure means a compound having at least one or more cations, anions, and an ethylenically unsaturated group in the same molecule. In the present invention, examples of the cation include cations such as quaternary ammonium, sulfonium, and phosphonium. Examples of the anion include -COO - , -PO4 2- , -HPO4 - , -SO3 -Examples of anions include:
[0078] In the present invention, the compound having a betaine structure contains a quaternary ammonium as a cation in the molecule and -SO3 as an anion. - Sulfobetaine containing quaternary ammonium as the cation and -PO4 as the anion in the molecule 2- Among them, phosphobetaines containing quaternary ammonium as a cation and -SO3 as an anion in the molecule are preferred. - More preferred is a sulfobetaine containing the following: Further preferred is a sulfobetaine having a (meth)acrylic skeleton in the molecule.
[0079] In the present invention, an example of a compound having a betaine structure is compound 1 represented by the following formula (I1). Compound 1: [ka] In Compound 1, L1 includes any one of -COO-, -CONH-, and -(CH2)m- (m is a natural number); R1 is H or CH3; R3 and R6 each independently represent -(CH2) l - (l is a natural number from 1 to 10), R4 and R5 are each independently a group containing C and H as essential components and O as an optional component, and not containing N or S. Incidentally, it is possible to specify that L1 contains -COO- from the above-mentioned IR.
[0080] In the present invention, an example of a compound having a betaine structure is compound 2 represented by the following formula (I2). Compound 2: [ka] In compound 2, L1 includes any one of -COO-, -CONH-, and -(CH2)m- (m is a natural number); R1 is H or CH3; R7 and R8 each independently represent -(CH2) l - (l is a natural number from 1 to 10), R9, R 10 , R 11 are each independently a group containing C and H as essential components and O as an optional component, and containing neither N nor S.
[0081] In the present invention, specific examples of compounds having a betaine structure include 3-[[2-(acryloyloxy)ethyl]dimethylammonio]propane-1-sulfonic acid, 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propane-1-sulfonic acid, 4-[(3-methacrylamidopropyl)dimethylammonio]butane-1-sulfonic acid, 2-(methacryloyloxy)ethyl 2-(trimethylammonio)ethyl] phosphate, 4-[[2-(methacryloyloxy)ethyl]dimethylammonio]butane-1-sulfonic acid, 3-[(3-acrylamidopropyl)dimethylammonio]propane-1-sulfonic acid, and 3-[(3-methacrylamidopropyl)dimethylammonio]propane-1-sulfonic acid. Among these, 3-[[2-(acryloyloxy)ethyl]dimethylammonio]propane-1-sulfonic acid, 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propane-1-sulfonic acid, [3-(methacryloylamino)propyl]dimethyl(3-sulfobutyl)ammonium hydroxide, and 2-(methacryloyloxy)ethyl 2-(trimethylammonio)ethyl phosphate are preferred.
[0082] 2-2-5-2. Polymerizable organic compounds other than betaine As a compound for adjusting the concentration of the betaine structure in the surface layer, the following hydrophilic polymerizable compounds and / or non-hydrophilic polymerizable organic compounds can be used. In the composition for forming the surface layer, the polymerizable organic substances other than betaine are N 2 O 3 obtained by XPS measurement of the surface of the member when the surface layer is formed by the manufacturing method of the member described later. + It is preferable that the atomic concentration is 0.3% or more and 2.8% or less, and the static contact angle of water with the surface of the surface layer is 35° or less.
[0083] 2-2-5-2-1. Hydrophilic polymerizable compounds As the hydrophilic polymerizable compound, one or more types selected from the nonionic monomers, anionic monomers and cationic monomers described below can be used.
[0084] 2-2-5-2-1-1.Nonionic monomers In the present invention, the surface layer forming composition can contain a nonionic monomer. This allows the surface layer obtained by curing the surface layer forming composition to contain a structure containing an organic component other than the structure represented by formula (A1). In the present invention, the nonionic monomer means a monomer having one or more ethylenically unsaturated groups and an oxyalkylene in the molecule. The nonionic monomer is hydrophilic. The nonionic monomer is more preferably a monomer having a (meth)acrylic skeleton and an oxyalkylene group in the molecule.
[0085] In the present invention, the nonionic monomer may be a monofunctional nonionic monomer represented by the following formula (J1). [ka] In formula (J1), L2 is -COO-, -CONH-, -(CH2) m - (where m is a natural number), R2 is H or CH3; R 12is H or CH3 or C2H5, Y is a linear, branched or cyclic hydrocarbon group having 1 to 10 carbon atoms; a is a natural number.
[0086] In the present invention, the nonionic monomer may be a bifunctional nonionic monomer having an oxyalkylene group, represented by the following formula (J2). [ka] In formula (J2), L2 is -COO-, -CONH-, -(CH2) m - (where m is a natural number), L3 is -OCO-, -NHCO-, -(CH2) m - (where m is a natural number), R2 is H or CH3; Y is a linear, branched or cyclic hydrocarbon group having 1 to 10 carbon atoms; a is a natural number.
[0087] In the present invention, the nonionic monomer may be a trifunctional nonionic monomer 1 having an oxyalkylene group, represented by the following formula (J3). [ka] In formula (J3), L3 is -OCO-, -NHCO-, -(CH2) m - (where m is a natural number), R2 is H or CH3; Y is a linear or cyclic hydrocarbon group having 1 to 10 carbon atoms; b, c, and d are each independent natural numbers.
[0088] In the present invention, the nonionic monomer may be a trifunctional nonionic monomer 2 having an oxyalkylene group, represented by the following formula (J4). [ka] In formula (J4), L3 is -OCO-, -NHCO-, -(CH2) m - (where m is a natural number), R2 is H or CH3; Y is a linear or cyclic hydrocarbon group having 1 to 10 carbon atoms; b, c, and d are each independent natural numbers.
[0089] In the present invention, the nonionic monomer may be a tetrafunctional nonionic monomer having an oxyalkylene group, represented by the following formula (J5). [ka] In formula (J5), L2 is -COO-, -CONH-, -(CH2) m - (where m is a natural number), L3 is -OCO-, -NHCO-, -(CH2) m - (where m is a natural number), R2 is H or CH3; Y is a linear or cyclic hydrocarbon group having 1 to 10 carbon atoms; b, c, d, and e are each independent natural numbers.
[0090] In the present invention, specific examples of nonionic monomers include 4-hydroxybutyl acrylate, 2-methoxyethyl acrylate (2-methoxyethyl acrylate), 2-[2-(2-methoxyethoxy)ethoxy]ethyl acrylate, 2-hydroxyethyl methacrylate (2-hydroxyethyl methacrylate (HEMA)), 2-methoxyethyl methacrylate, diethylene glycol monomethyl ether methacrylate, hydroxypropyl methacrylate, 2-hydroxybutyl methacrylate, N-(hydroxymethyl)acrylamide, N-(2-hydroxyethyl)acrylamide, N-(methoxymethyl)acrylamide, N-(methoxymethyl)methacrylamide, N-(hydroxymethyl)methacrylamide, and methoxydiethylene glycol. Methacrylate, methoxytetraethylene glycol methacrylate, methoxypolyethylene glycol methacrylate, methoxypolyethylene glycol acrylate, polyethylene glycol methacrylate, N-(4-hydroxyphenyl)methacrylamide, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, alkoxylated trimethylolpropane acrylate, alkoxylated trimethylolpropane methacrylate, alkoxylated glycerin acrylate, alkoxylated glycerin methacrylate, alkoxylated pentaerythritol tetraacrylate, and alkoxylated pentaerythritol tetramethacrylate. Of these, 2-hydroxyethyl methacrylate (HEMA), methoxytetraethylene glycol methacrylate, methoxypolyethylene glycol methacrylate, 2-methoxyethyl acrylate, and diethylene glycol dimethacrylate are preferred. More preferred are 2-hydroxyethyl methacrylate (HEMA) and methoxypolyethylene glycol methacrylate.
[0091] 2-2-5-2-1-2.Anionic monomers In the present invention, the composition for forming a surface layer can contain an anionic monomer. This allows the surface layer obtained by curing the composition for forming a surface layer to contain a structure containing an organic component other than the structure represented by formula (A1). In the present invention, the anionic monomer means a compound having at least one or more anions and ethylenically unsaturated groups in the molecule. In the present invention, the anion is -COO - , -PO4 2- , -HPO4 - , -SO3 - Examples of anions include:
[0092] In the present invention, examples of the anionic monomer include anionic monomers represented by the following formulae (K1) and (K2). [ka] In formula (K1), L2 is -COO-, -CONH-, -(CH2) m -(m is a natural number), -Ph-, R2 is H or CH3; M1 represents a hydrogen ion, an ammonium ion, or an alkali metal ion. [ka] In formula (K2), L2 is -COO-, -CONH-, -(CH2) m -(m is a natural number), -Ph-, R2 is H or CH3; R 13 is a group containing C and H as essential components and O as an optional component, but not containing N or S, M1 represents a hydrogen ion, an ammonium ion, or an alkali metal ion.
[0093] In the present invention, specific examples of the anionic monomer include 2-((meth)acryloyloxy)ethanesulfonic acid, potassium 2-((meth)acryloyloxy)ethanesulfonate, sodium 2-((meth)acryloyloxy)ethanesulfonate, 3-((meth)acryloyloxy)propane-1-sulfonic acid, potassium 3-((meth)acryloyloxy)propane-1-sulfonate, sodium 3-((meth)acryloyloxy)propane-1-sulfonate, 2-acrylamido-2-methylpropanesulfonic acid, potassium 2-acrylamido-2-methylpropanesulfonate, sodium 2-acrylamido-2-methylpropanesulfonate, styrenesulfonic acid, potassium styrenesulfonate, and sodium styrenesulfonate.
[0094] 2-2-5-2-1-3.Cationic monomers In the present invention, the cationic monomer may be represented by the following formula (L). [ka] In formula (L), L2 is -COO-, -CONH-, -(CH2) m - (where m is a natural number), R2 is H or CH3; R 14 is -(CH2) l - (l is a natural number from 1 to 10), R 15 , R 16 , R 17 are each independently a group containing C and H as essential components and O as an optional component, but not containing N or S, M2 represents any one of a hydroxide ion, a fluorine ion, a chloride ion, a bromide ion, and an iodine ion.
[0095] In the present invention, specific examples of the cationic monomer include N-(2-(meth)acryloyloxyethyl)-N-benzyl-N,N-dimethylammonium chloride, (3-(meth)acrylamidopropyl)trimethylammonium chloride, and N-(2-(meth)acryloyloxyethyl)-N-benzyl-N,N-dimethylammonium chloride.
[0096] 2-2-5-2-2.Non-hydrophilic polymerizable compounds In the present invention, the non-hydrophilic polymerizable compound may be a non-polar monomer.
[0097] In the present invention, the non-polar monomer may be a monofunctional non-ionic monomer having a hydrocarbon group, represented by the following formula (M). [ka] In formula (M), L2 is -COO-, -CONH-, -(CH2) m - (where m is a natural number), R2 is H or CH3; R 18 is a straight-chain or cyclic hydrocarbon group having 1 to 10 carbon atoms.
[0098] In the present invention, specific examples of non-polar monomers include allyl acrylate, allyl methacrylate, ethyl acrylate, ethyl methacrylate, ethyl acrylamide, ethyl methacrylamide, propyl acrylate, propyl methacrylate, propyl acrylamide, propyl methacrylamide, isopropyl acrylate, isopropyl methacrylate, isopropyl acrylamide, isopropyl methacrylamide, butyl acrylate, butyl methacrylate, butyl acrylamide, butyl methacrylamide, isobutyl acrylate, isobutyl methacrylate, isobutyl acrylamide, isobutyl methacrylamide, tert-butyl acrylate, isobutyl methacrylate, isobutyl acrylamide, isobutyl methacrylamide, and tert-butyl acrylate. Examples of the acrylic acid ester include t-butyl acrylate, tert-butyl methacrylate, tert-butyl acrylamide, tert-butyl methacrylamide, hexyl acrylate, hexyl methacrylate, hexyl acrylamide, hexyl methacrylamide, cyclohexyl acrylate, cyclohexyl methacrylate, cyclohexyl acrylamide, cyclohexyl methacrylamide, benzyl acrylate, benzyl methacrylate, benzyl acrylamide, benzyl methacrylamide, 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate, 2-ethylhexyl acrylamide, and 2-ethylhexyl methacrylamide.
[0099] In the present invention, the composition for forming a surface layer can contain a component contained in the composition for forming an intermediate layer described later. In other words, the component contained in the composition for forming an intermediate layer is contained in the composition for forming a surface layer, thereby increasing the adhesion between the surface layer and the substrate. In this case, it is necessary to form a film so that the structure represented by formula (A1) is sufficiently contained in the surface layer. For example, by adding an additive such as a surfactant to the composition, it is possible to cause the structure represented by formula (A1) to be segregated at an inclination on the surface. Here, the surfactant preferably has a hydrophilic portion and a hydrophobic portion consisting of an organic residue, and has a molecular weight of less than 10,000.
[0100] When the composition for forming a surface layer contains a component contained in the composition for forming an intermediate layer, the composition preferably contains a compound having a betaine structure in a weight concentration range of 0.01% to 10%. In addition, the composition preferably contains a polyfunctional acrylate or polyfunctional vinyl compound described below in a range of 1% to 99%. Furthermore, the composition preferably contains a surfactant described below in a range of 0% to 10%. In addition, the composition may contain a nonionic monomer, an anionic monomer, a cationic monomer, and a nonpolar monomer in a range of 0% to 10%. Incidentally, containing 0% is synonymous with not containing the target component.
[0101] When this composition is used to form a film, it is preferable that the concentration of Si atoms obtained by XPS measurement of the surface of the surface layer is 1.0% or less, and furthermore, the concentration of Si atoms obtained by XPS measurement of a region from the surface of the surface layer to a point 1 μm deep is 1.0% or less. For this purpose, it is preferable that the composition contains a compound containing Si atoms in a weight concentration range of 0% to 1%, and more preferably 0%.
[0102] 2-2-5-3.Solvent In the present invention, the composition for forming a surface layer may contain a solvent. This can improve the wettability to the substrate or adjust the viscosity of the composition for forming a surface layer. As the solvent, alcohols such as methanol, ethanol, IPA (isopropanol), and n-butanol, cellosolves such as 2-methoxyethanol and methoxypropanol, ketones such as acetone, DMF (N,N'-dimethylformamide), water, etc. can be used, but are not limited to these. In addition, multiple types of solvents may be mixed and used as necessary. In addition, the solvent can also be used when preparing the composition for forming a primer layer and the composition for forming an intermediate layer, which will be described later.
[0103] 2-2-5-4. Polymerization initiator The surface layer-forming composition preferably contains a polymerization initiator. As the polymerization initiator, known ones can be used, for example, a photopolymerization initiator or a thermal polymerization initiator.
[0104] Preferred examples of the photopolymerization initiator include Irgacure 651, Irgacure 184, Irgacure 500, Irgacure 2959, Irgacure 127, Irgacure 907, Irgacure 369, Irgacure 1300, Irgacure 819, Irgacure 1800, Irgacure OXE01, Irgacure OXE02, Darocur 1173, Darocur TPO, and Darocur 4265, all of which are available from BASF.
[0105] As a preferred example of the thermal polymerization initiator, a thermal radical generator such as a peroxide, a persulfate, or an azo compound is preferably used.
[0106] 2-2-5-5.Additives In addition to the above, the surface layer forming composition may contain known additives such as surfactants depending on the purpose, within the range that does not impair the function of the surface.
[0107] 2-2-6. Middle class In the present invention, in order to further strengthen the adhesion between the substrate 11 and the surface layer 12, an intermediate layer 13 may be formed between the substrate 11 and the surface layer 12. In order to obtain strong adhesion with the surface layer 12, which is an organic film, the intermediate layer 13 preferably contains a main chain of an acrylic resin (polyacrylic copolymer) or a polyvinyl copolymer containing vinyl alcohol.
[0108] 2-2-7. Composition for forming intermediate layer In the present invention, the intermediate layer 13 is preferably formed by curing a composition for forming an intermediate layer. The composition for forming an intermediate layer preferably contains a monomer capable of forming a polyacrylic or polyvinyl copolymer. The composition for forming an intermediate layer preferably further contains the above-mentioned solvent and polymerization initiator.
[0109] 2-2-7-1. Multifunctional acrylate As a monomer constituting the polyacrylic copolymer, a multifunctional acrylate can be suitably used. In the present invention, the multifunctional acrylate means a monomer having at least two or more ethylenically unsaturated groups in the molecule. Specific examples of the multifunctional acrylate include 2-hydroxy-3-acryloyloxypropyl methacrylate, propoxylated ethoxylated bisphenol A diacrylate, ethoxylated bisphenol A diacrylate, 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene, propoxylated bisphenol A diacrylate, tricyclodecane dimethanol diacrylate, 1,10-decane diol diacrylate, 1,6-hexanediol diacrylate, 1,9-nonane diol diacrylate, and the like. All diacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, ethoxylated isocyanuric acid triacrylate, ε-caprolactone modified tris-(2-acryloxyethyl) isocyanurate, pentaerythritol triacrylate, trimethylolpropane triacrylate, ditrimethylolpropane trimethacrylate, ethoxylated glycerin triacrylate, ethoxylated pentaerythritol tetraacrylate, ditrimethylolpropane trimethacrylate Pantaerythritol tetraacrylate, dipentaerythritol hexaacrylate, ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, 2,2 bis [4- (methacryloxyethoxy) phenyl] propane, tricyclodecane dimethanol dimethacrylate, 1,10-decanediol dimethacrylate, 1,6-hexanediol methacrylate, 1,9-nonanediol methacrylate, neopentyl glycol methacrylate, glycerin dimethacrylate, trimethylolpropane trimethacrylate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, polypropylene glycol diacrylate, polytetramethylene glycol diacrylate, glycerin triacrylate ethoxylate, dipentaerythritol polyacrylate, ethoxylated polypropylene glycol dimethacrylate, polypropylene dimethacrylate, and the like.
[0110] In addition, the polyfunctional acrylate may be a urethane (meth)acrylate oligomer (polymer) having two or more ethylenically unsaturated groups. For example, it may be phenyl glycidyl ether acrylate hexamethylene diisocyanate urethane prepolymer, phenyl glycidyl ether acrylate toluene diisocyanate urethane prepolymer, pentaerythritol triacrylate hexamethylene diisocyanate urethane prepolymer, pentaerythritol triacrylate toluene diisocyanate urethane prepolymer, pentaerythritol triacrylate isophorone diisocyanate urethane prepolymer, dipentaerythritol pentaacrylate hexamethylene diisocyanate urethane prepolymer, oligourethane acrylate, carboxylic acid-containing urethane acrylate oligomer, etc.
[0111] In addition, examples of polyfunctional acrylates include epoxy (meth)acrylate oligomers (polymers) having two or more ethylenically unsaturated groups, such as cresol novolac type epoxy acrylates and carboxylic anhydride modified epoxy acrylates.
[0112] In the present invention, a specific example of a preferred polyfunctional acrylate is one in which the functional group equivalent of the ethylenically unsaturated group is 200 g / eq or less. This allows a primer layer with high durability to be obtained. The functional group equivalent of the ethylenically unsaturated group is preferably 150 g / eq or less, more preferably 27 g / eq or more and 150 g / eq or less. This allows a primer layer with higher durability to be obtained. Here, the functional group equivalent represents the molecular weight of a compound per functional group. That is, it is a value obtained by dividing the molecular weight of the polyfunctional acrylate by the number of ethylenically unsaturated groups. Specifically, it is a value obtained by dividing the molecular weight of the polyfunctional acrylate, which is a (meth)acrylate monomer (oligomer), a urethane modified product thereof, a urethane (meth)acrylate monomer (oligomer), and an epoxy modified product thereof, an epoxy (meth)acrylate monomer (oligomer), by the number of (meth)acryloyl groups, which are ethylenically unsaturated groups. Examples of compounds satisfying such functional group equivalents include pentaerythritol tetraacrylate (88 g / eq), dipentaerythritol tetraacrylate (105 g / eq), dipentaerythritol hexaacrylate (96 g / eq), trimethylolpropane triacrylate (99 g / eq), trimethylolpropane tetraacrylate (117 g / eq), 1,3,5-tris(2,2-diacryloyloxymethyl-3-(2,2,2-triacryloyloxymethylethoxy)propylhexylcarbamate)isocyanurate (153 g / eq), and ethoxylated dipentaerythritol hexaacrylate (185 g / eq).
[0113] Among these, those having six or more functional groups in one molecule are particularly preferred in order to further enhance the durability of the intermediate layer, and examples thereof include dipentaerythritol hexaacrylate (6 functional), ethoxylated dipentaerythritol hexaacrylate (6 functional), and 1,3,5-tris(2,2-diacryloyloxymethyl-3-(2,2,2-triacryloyloxymethylethoxy)propylhexylcarbamate)isocyanurate (15 functional).
[0114] 2-2-7-2. Multifunctional vinyl compounds As a monomer constituting the polyvinyl copolymer, a multifunctional vinyl compound can be suitably used. In the present invention, the multifunctional vinyl compound means a monomer having at least two ethylenically unsaturated groups in the molecule. Specific examples of the multifunctional vinyl compound include diallyl ether, diethylene glycol divinyl ether, 1,3-diallyloxy-2-propanol, 1,2,3-triallyloxy-2-propanol, 2,2 bisallyloxymethyl-1-propanol, 2,2 bisallyloxyethyl-1-butanol, 2,2 bisallyloxymethyl-1-hexanol, 3,3 bisallyloxyethyl-1-butanol, 3,3 bisallyloxyethyl-1-hexanol, 2, Examples of such alkyl ethers include 2,2-aryloxymethyl-1-ethanol, 2,2,2-aryloxymethyl-1-propanol, 2,2,2-aryloxymethyl-1-butanol, 2,2,2-aryloxymethyl-1-hexanol, 1,5-hexadiene-3,4-diol, diallyl isophthalate, 1,5-hexanediene, tetraallyloxyethane, tetraallyloxypropane, tetraallyloxybutane, triallyl citrate, and divinyl adipate.
[0115] The surfactant is preferably a polymerizable surfactant in order to improve the wettability of the surface. Examples of the polymerizable surfactant include polyoxypropylene allyl ether phosphate ester, ammonium salt of sulfuric acid and ethoxylated allyl alkyl glyceryl ether ester, polyoxyalkylene alkenyl ether, sodium alkyl allyl sulfosuccinate, polyoxyethylene-1-(allyloxymethyl) alkyl ether sulfate ester ammonium salt, and amine salt.
[0116] In the present invention, the film thickness including the surface layer and the intermediate layer is preferably in the range of 0.1 μm to 200 μm. Thereby, the effect of reducing the protein adsorption force can be sufficiently exhibited, and sliding durability can be provided. The film thickness including the surface layer and the intermediate layer is more preferably in the range of 1 to 100 μm, and even more preferably in the range of 1 to 20 μm.
[0117] The film thickness of the surface layer can be measured by cross-sectional observation using SEM or the like.
[0118] <Film thickness measurement by SEM> · SEM apparatus As the SEM apparatus, Regulus8220 (manufactured by Hitachi High-Technologies Corporation) can be used and measurement can be performed under the following conditions. · SEM measurement conditions Acceleration voltage: 1 kV Magnification: 20000 to 400 times
[0119] 2-2-8.Primer layer In the present invention, when the base material 11 is an inorganic material such as glass, pottery, or metal, a primer layer 14 may be formed in order to strengthen the adhesion between these inorganic materials and the surface layer 12. The primer layer 14 is preferably formed between the inorganic material that is the base material 11 (hereinafter referred to as "inorganic base material") and the surface layer 12. In order to enhance the adhesion force, the primer layer 14 needs to bond to both the inorganic base material and the surface layer 12. For this reason, the primer layer 14 is preferably a layer containing Si atoms.
[0120] 2-2-9. Primer layer forming composition The primer layer 14 is preferably formed by curing a composition for forming a primer layer. As the composition for forming a primer layer, those containing commonly used silane-based or phosphoric acid-based coupling agents can be used. Further, in order to make the adhesion to the surface layer stronger, these coupling agents preferably contain ethylenically unsaturated groups such as acryloyl groups and methacryloyl groups.
[0121] 2-2-9-1.Silane compounds Silane compound can be suitably used as silane coupling agent. In the present invention, silane compound means an organic compound having hydrolyzable Si-OR group (reactive silyl group, OR can be hydroxyl group or hydrolyzable group. Hydrolyzable group is, for example, alkoxy group, halogeno group. Specifically, -OCH3, -OCH2CH3, -Cl can be mentioned.). Specific examples of silane compounds include tetraethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropyltrimethoxysilane, 8-methacryloxyoctyltrimethoxysilane, 3-methacryloxymethyltriethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxymethyltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, Silane, 3-glycidoxypropyltriethoxysilane, p-styryltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, tris-(trimethoxysilylpropyl)isocyanurate, 3-ureidopropyltrialkoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-isocyanatopropyltriethoxysilane, 3-trimethoxysilylpropylsuccinic anhydride, and the like.
[0122] In the present invention, a specific example of a preferred silane compound is a compound having three or more hydrolyzable Si-OR groups for adhering to an inorganic substrate and an acrylic or methacrylic polymerizable functional group for adhering to a surface layer that is an organic film. Examples of such silane compounds include 3-acryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropyltrimethoxysilane, 8-methacryloxyoctyltrimethoxysilane, 3-methacryloxymethyltriethoxysilane, 3-methacryloxypropyltriethoxysilane, and 3-methacryloxymethyltrimethoxysilane.
[0123] 2-2-9-2.Phosphate compounds As the phosphate coupling agent, a phosphate compound can be preferably used. In the present invention, the phosphate compound is a compound having a covalent bond P(OH) n It means an organic compound having a group (adsorbent phosphate group, n is any one of 1 to 3, and OH group may be its base substitute such as ONa, OK, ONH4, etc.). As the phosphate compound, those containing phosphoric acid or a phosphate as an adsorbent functional group and an acryl group, methacryl group, or vinyl group as a polymerizable functional group in the molecule are preferable. Specific examples include 2-acryloxyethyl phosphoric acid, 2-acryloxyethyl phosphoric acid, 2-methacryloxyethyl phosphoric acid, 2-methacryloxyethyl phosphoric acid, 2-acryloxypropyl phosphoric acid, 2-acryloxypropyl phosphoric acid, 2-methacryloxypropyl phosphoric acid, 2-methacryloxypropyl phosphoric acid, 2-methacryloxypropyl phosphoric acid, vinyl phosphoric acid, 2-acryloxybutyl phosphoric acid, 2-acryloxybutyl phosphoric acid, 2-methacryloxybutyl phosphoric acid, 2-methacryloxybutyl phosphoric acid, vinyl phosphoric acid, or their phosphates.
[0124] 2-2-10.Optional ingredients To the surface layer, the intermediate layer, and the primer layer, various additives such as ultraviolet absorbers, light stabilizers, antioxidants, leveling agents, defoaming agents, thickeners, anti-settling agents, and dyes, pigments, and matting agents that control the design properties of the coating can be added within a range that does not inhibit the antifouling properties of the member.
[0125] 2-2-11. Excellent composition for long-term water stain removal In a preferred embodiment of the present invention, in order to maintain the scale removal property over a long period, it is preferable that the concentration of Si atoms obtained by XPS measurement in the region from the surface of the surface layer to a depth of 1 μm is 1.0% or less, and more preferably 0.8% or less. Thereby, even when the surface is worn due to long-term use and the intermediate layer is exposed, the formation and adsorption of scale can be suppressed.
[0126] As described above, for the purpose of increasing the density of the polymer, increasing the hydrophilicity, increasing the adhesion to the substrate, etc., for example, Patent Document 3 discloses a technique for synthesizing a polymer containing zwitterions by silane coupling, and Patent Document 5 discloses a technique for providing a hydrophilic layer of 1 μm or less on the intermediate layer of a siloxane polymer. However, in these techniques, when the surface is worn due to long-term use of the member or structure, the Si component in the intermediate layer or the substrate is exposed on the surface, making it easy to form scale, so it is considered that the effect cannot be exerted over a long period.
[0127] The concentration of Si atoms in the region from the surface of the surface layer to a depth of 1 μm can be measured by the following method.
[0128] <Gas Cluster Ion Beam - X-ray Photoelectron Spectroscopy (GCIB-XPS)> The surface layer is sputtered with Ar gas cluster ions, the surface exposed at each specific sputtering time is measured by XPS, and the concentration of Si atoms can be calculated.
[0129] <XPS Measurement> · Preparation of Measurement Sample A flat plate-shaped region cut from a member sample with an appropriate size can be used as a measurement sample. It is preferable to clean the surface of the measurement sample before measurement. For example, it is more preferable to clean the surface of the measurement sample using a neutral detergent and a sponge, then perform ultrasonic cleaning with ultrapure water, and finally thoroughly rinse with ultrapure water. ·XPS measurement device For the XPS measurement device, QUANTERA II (manufactured by ULVAC-PHI, Inc.) can be used. ·XPS measurement conditions X-ray conditions: Monochromatic AlKα ray, 25W - 15KV Photoelectron extraction angle: 45° Analysis area: 100μmφ Neutralization gun conditions: Auto Neutralizer Ion gun conditions: Auto Neutralizer (narrow) Time per step: 50ms Energy step size: 0.100eV Sweep: 5 times Pass energy: 55eV Scanning range: C1s peak 279.000eV - 299.000eV, O1s peak 525.000eV - 545.000eV, N1s peak 392.000eV - 410.000eV, S2p peak 157.000eV - 177.000eV, P2p peak 124.000eV - 144.000eV ·GCIB sputtering conditions The following conditions can be used for GCIB sputtering. Beam voltage: 10kV Beam current: 30nA
[0130] <Calculation of atomic concentration of Si> The atomic concentration of the detected elements can be calculated from the obtained spectrum using, for example, data analysis software MultiPaK (version 9.0, manufactured by ULVAC-PHI, Inc.). The spectrum obtained by XPS measurement is charge-corrected with the C1s peak set at 284.5 eV. Then, the background is removed by the Shirley method for the peaks based on the electron orbitals of each measured atom, and the peak area intensity is calculated. An analysis process is performed in which the peaks are divided by the sensitivity coefficient specific to the device that is preset in the data analysis software, and the atomic concentration of Si is calculated when the sum of C atoms, O atoms, N atoms, S atoms, Si atoms, and P atoms is set to 100%.
[0131] The sputter rate can be calculated by dividing the actual depth of the sputter marks on the sample after measurement, which is observed with a laser microscope, by the sputter time. Also, the depth at that point can be calculated by integrating the sputter time and the sputter rate.
[0132] 2-3. Manufacturing method of components The member according to the present invention can be produced, for example, by the following method.
[0133] 2-3-1. Preparation of the substrate A substrate is prepared. In the present invention, it is preferable to pretreat the substrate. For example, it is preferable to wash the substrate with a neutral detergent and rinse with ion-exchanged water or ultrapure water. Any water droplets remaining on the substrate surface are preferably dried using an air blower or a dryer.
[0134] 2-3-2. Preparation of the composition for forming the surface layer A compound having a structure represented by formula (A1) (a compound having a betaine structure) and other components are mixed in an arbitrary ratio and dissolved in a solvent. A polymerization initiator is added to this solution and stirred to obtain a composition for forming a surface layer. The weight concentration of the compound having a structure represented by formula (A1) is preferably 0.5% to 20%. When a polymerizable organic compound other than betaine is contained as an optional component, the total weight concentration of the compound having a structure represented by formula (A1) and the polymerizable organic compound other than betaine is preferably 0.5% to 20%, and the weight concentration ratio of each in the composition is preferably 95:5 to 5:95.
[0135] 2-3-3. Application of the composition for forming the surface layer The composition for forming a surface layer is applied onto the substrate. A known method may be used as the application method. For example, the composition can be applied by a general method such as brush coating, spray coating, dip coating, spin coating, curtain coating, bar coating, etc. The coating amount can be adjusted according to these application conditions to adjust the film thickness of the resulting cured product. In the present invention, the film thickness of the formed surface layer (or including both the surface layer and the intermediate layer) is preferably in the range of 0.1 μm to 200 μm. This allows for a sufficient effect of suppressing the adhesion of protein and the adhesion of water stains, and further allows for the development of sliding durability. The film thickness of the surface layer (or including both the surface layer and the intermediate layer) is more preferably in the range of 1 to 100 μm, and even more preferably in the range of 1 to 20 μm.
[0136] 2-3-4. Drying The surface layer forming composition applied on the substrate is dried. In the present invention, when the surface layer forming composition contains a solvent, it is preferable to dry the surface layer forming composition after applying it on the substrate in order to dry the solvent. In addition, in consideration of the productivity of the member, drying by heating can be preferably used.
[0137] 2-3-5. Hardening The surface layer forming composition applied on the substrate is cured. Examples of the curing means include heat curing, active energy ray curing, and a combination of heat curing and active energy ray curing. When heat curing is performed, a known thermal polymerization initiator can be used as the polymerization initiator, and a known method of heating with infrared rays or hot air can be used. In addition, in the case of active energy ray curing, examples of the radiation include visible light of 400 to 800 nm, ultraviolet light of 400 nm or less, and electron beams. Usually, relatively inexpensive ultraviolet light or visible light is preferably used rather than electron beams, which require expensive equipment. When active energy ray curing is performed using ultraviolet light or visible light, a known photopolymerization initiator can be used. When ultraviolet light is used, examples of the ultraviolet light generating source include low pressure mercury lamps, high pressure mercury lamps, ultra-high pressure mercury lamps, xenon lamps, gallium lamps, metal halide lamps, ultraviolet lasers, and ultraviolet light such as sunlight. The irradiation atmosphere may be air or an inert gas such as nitrogen or argon.
[0138] 2-3-6. Formation of the intermediate layer In the present invention, the intermediate layer 13 may be formed on the substrate 11 before the surface layer 12 is formed on the substrate 11. This can further strengthen the adhesion between the substrate 11 and the surface layer 12. The composition for forming the intermediate layer can be prepared, for example, by adding a polymerization initiator to a solution in which the monomer capable of forming the above-mentioned polyacrylic or polyvinyl copolymer and a solvent are dissolved at an arbitrary weight ratio, and stirring the solution. The intermediate layer 13 can then be formed by applying the prepared composition for forming the intermediate layer on the substrate 11, drying, and curing it.
[0139] The thickness of the intermediate layer can be adjusted by the coating conditions, similarly to the surface layer. In the present invention, the thickness of the formed intermediate layer (or including both the surface layer and the intermediate layer) is preferably in the range of 0.1 μm to 200 μm. This provides a sufficient effect of suppressing the adhesion of proteins and the fixation of water stains, and also allows the sliding durability to be exhibited. The thickness of the intermediate layer (or including both the surface layer and the intermediate layer) is more preferably in the range of 1 to 100 μm, and even more preferably in the range of 1 to 20 μm.
[0140] 2-3-7. Formation of primer layer In the present invention, when the substrate 11 is an inorganic material such as glass, pottery, or metal, a primer layer 14 may be formed on the inorganic substrate before forming the intermediate layer 13 on the inorganic substrate. This can further strengthen the adhesion between the inorganic substrate and the surface layer 12. The composition for forming the primer layer can be prepared, for example, by dissolving the above-mentioned coupling agent and solvent, and, if necessary, a catalyst for promoting the hydrolysis reaction in any weight ratio, and stirring the mixture. Thereafter, the prepared composition for forming the primer layer is applied to the inorganic substrate and dried to form the primer layer 14.
[0141] 3. Reformed water The modified water in the present invention is water that has been modified so as to inhibit the adhesion or growth of dirt.
[0142] The modified water may be, for example, sterilized water or deionized water. The modified water may be used alone or in combination. When the modified water is used in combination, it may be mixed and discharged, or may be discharged from individual discharge ports. It is also possible to discharge a plurality of modified waters from a common discharge port by switching between them.
[0143] 3-1. Sterilized water Sterilizing water is water that has a bactericidal effect, i.e., can kill microorganisms such as bacteria. Examples of such water include water containing free chlorine (hypochlorous acid (HClO) and hypochlorite ions (ClO -), ozone water (water containing ozone), metal ion water (water containing metal ions such as silver ions, copper ions, and zinc ions), and water containing a bactericidal agent.
[0144] By using sterilizing water, it is possible to suppress the growth of microorganisms on the surface of a component, and it is possible to suppress the occurrence of microbial stains and the growth of stains caused by the growth of microorganisms. As mentioned above, if stains are attached to the surface of a component, the effect of sterilizing water is weakened, but the surface of the component in the present invention contains a betaine structure, which can suppress the adhesion of stains, and is hydrophilic, so that the discharged sterilizing water can be effectively wetted and spread. As a result, it is possible to suppress the growth of microbial stains and keep the surface of the component clean for a long period of time.
[0145] 3-2. Deionized water In the present invention, deionized water refers to tap water that has been treated to reduce the amount of ionic components. By discharging water with reduced ionic components onto the surface of a component, it is possible to inhibit adhesion of ionic components to the surface of the component, i.e., the generation of starting points for dirt and the growth of dirt that originates from these starting points. The surface of the component in the present invention contains a betaine structure, which exhibits an excellent adhesion inhibition effect, particularly against hydrophobic dirt and proteinaceous dirt. On the other hand, the cationic N + The site contains anions such as silicate ions and anionic SO3 - Site, PO4 ― There is a risk that cations such as calcium ions will be electrostatically adsorbed to the surface. As mentioned above, as the amount of these components that adhere increases, that is, as the adhesion density increases, scale will form on the surface, and the scale and dirt that originates from it may grow. By discharging deionized water onto the surface of the component, it is possible to suppress the adhesion of such ionic components and the growth of dirt that originates from them, and to keep the surface of the component clean for a long period of time.
[0146] 4. Reformed water generating device 2 The reformed water is generated by a reformed water generating device 2 included in the facility according to the present invention. There are no particular limitations on the method for generating the reformed water, but for example, the reformed water can be generated by electrolyzing tap water.
[0147] Tap water contains chloride ions, and by electrolyzing the chloride ions, free chlorine can be generated, making it possible to obtain free chlorine water.
[0148] It is also possible to generate ozone by electrolyzing tap water, thereby obtaining ozone water.
[0149] Furthermore, by performing electrolysis using metals such as silver, copper, and zinc as the anode, it is possible to produce water containing ions of these metals.
[0150] Furthermore, when water is electrolyzed, an anion oxidation reaction occurs at the cathode, and a cation reduction reaction occurs at the anode. In other words, each ion can be removed from the water to produce deionized water. The reformed water can also be produced by ion exchanging tap water.
[0151] In the present invention, it is more preferable that the reformed water is produced by electrolyzing tap water. By producing the reformed water by electrolysis of tap water, it is possible to eliminate the need for management such as replenishing chemicals, which is more convenient for users than when, for example, chemicals are used.
[0152] The reformed water generating device 2 may be provided between the tap water supply pipe and the reformed water discharge unit 3, and may be provided in a location where it can be supplied with the current required for control. It is desirable to install it in a manner that ensures ease of operation during maintenance and replacement, while preventing users from accidentally touching it; for example, it may be housed in a cover together with the reformed water discharge unit.
[0153] 4-1. Electrolytic section 1' In one embodiment of the reformed water generating apparatus 2 of the present invention, the electrolysis unit included in the reformed water generating apparatus 2 may be, for example, as shown in Fig. 3. The electrolysis unit 1' shown in Fig. 3 includes an electrolytic cell 2' and a control unit 3'. The electrolysis unit 1' generates and discharges reformed water. The configuration, control, and action of the electrolysis unit 1' will be described below.
[0154] 4-1-1. Electrolytic cell 2' The electrolytic cell 2' includes an inlet 21 through which tap water flows in, a water passage 22 communicating with the inlet 21, an electrode 231 provided midway through the water passage 22 for electrolyzing the inflowing tap water, and an outlet 24 provided downstream of the water passage 22 and downstream of the electrode 231.
[0155] Tap water flows into the electrolytic cell 2' through the inlet 21 .
[0156] The water passage 22 may be provided, for example, with a sealable material so that tap water flowing into the electrolytic cell 2' does not leak out.
[0157] The electrode 231 is an electrode pair, and is composed of an anode 2311 and a cathode 2312. The anode 2311 and the cathode 2312 may both be in the form of a plate, for example. Tap water is electrolyzed between the anode and the cathode. In one embodiment of the present invention, when tap water is electrolyzed, both free chlorine (i.e., hypochlorous acid molecules (HClO, a in FIG. 3) and hypochlorite ions (ClO-, b in FIG. 3)) are generated simultaneously. In one embodiment of the present invention, tap water can be electrolyzed to generate ozone, and water containing these metal ions can be generated by electrolyzing the water using a metal electrode containing silver, copper, zinc, etc. as the anode 2311. In another embodiment of the present invention, as shown in FIG. 4, an electric current is passed through tap water to deposit anionic components (c in FIG. 4) in the water on the anode 2311 and cationic components (d in FIG. 4) on the cathode 2322, thereby reducing the ionic components in the aqueous solution.
[0158] The electrolytic layer can be a continuous electric deionization layer by combining an ion exchange membrane and an ion exchange resin. This prevents the electrodes from deteriorating due to the deposition of ionic components, and makes it unnecessary to regenerate the ion resin, making it possible to eliminate the need for maintenance of the electrolytic layer. When a continuous electric deionization layer is used, it is desirable to discharge the water in which the ionic components are concentrated into a drain pipe.
[0159] The outlet 24 discharges the produced reformed water to the outside of the electrolytic cell 2'. The outlet 24 is preferably in communication with a reformed water discharge section 3 (FIG. 1) that allows the reformed water to come into contact with a surface of a component.
[0160] 4-1-2. Control unit 3' The control unit 3' has a function of generating reformed water by electrolysis by passing electricity through the electrode 231, and a function of controlling the concentration of the reformed water by controlling both or either one of the voltage and the current. The control unit 3' may also have a function of controlling the opening and closing of the solenoid valve for tap water flowing in from the inlet 21, the opening and closing of the solenoid valve for reformed water flowing out from the outlet 24, manual / automatic switches, various sensors, etc., so that they operate appropriately. It is preferable that the control unit 3' further has a function of controlling so that the reformed water is discharged from the reformed water discharge unit 3 so as to come into contact with the surface of a component.
[0161] 4-2.Ion exchange unit In one embodiment of the reformed water generating apparatus of the present invention, the reformed water generating apparatus may be equipped with an ion exchange section. In the ion exchange section, cations and / or anions in tap water are captured by an ion exchange resin, and each of them is converted to H + , O.H. - By releasing this, the ionic components in tap water can be reduced.
[0162] 5.Reformed water discharge section The reformed water prepared by the reformed water generating device is discharged toward the surface of the component from the reformed water discharging unit 3. The reformed water discharging unit 3 is only required to be able to spray the reformed water onto a predetermined area of the surface of the component, and there are no particular limitations on the form or method of discharging. EXAMPLES
[0163] The present invention will be described in more detail with reference to the following examples, but the present invention is not limited to these examples.
[0164] 1. Base material Bathroom floor sheet: Made of glass fiber reinforced polypropylene resin, 14mm square tile pattern, 21cm x 30cm x 2mm thick.
[0165] 2. Reagents The following reagents were prepared: <Multifunctional acrylate> Dipentaerythritol polyacrylate <Polymerization initiator> A mixture of 1-hydroxycyclohexyl phenyl ketone and benzophenone in a weight ratio of 1:1 (BASF Irgacure 500) <Solvent> 2-Methoxyethanol <Compounds with betaine structure> 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propane-1-sulfonic acid <Nonionic compounds> 2-Hydroxyethyl methacrylate (2-Hydroxyethyl methacrylate (HEMA)) <Compounds having sulfonic acid groups> Potassium 3-sulfopropyl methacrylate <Surfactant> Sodium di-2-ethylhexyl sulfosuccinate (Aerosol OT)
[0166] 3. Preparation of component samples Sample members 1 to 3 were prepared as follows.
[0167] Material sample 1 3-1. Pretreatment of substrate The surface of the substrate was washed with a neutral detergent, rinsed with tap water, and then rinsed with ion-exchanged water. Water droplets on the surface of the substrate were blown off with an air blower, and the substrate was dried.
[0168] 3-2. Formation of the surface layer 3-2-1. Preparation of the composition for forming the surface layer The compound having a betaine structure was dissolved in the solvent at 1%, the polyfunctional acrylate at 30%, the polymerization initiator at 0.75%, and the surfactant at 0.05% by mass. Acrylic resin particles (Art Pearl SE-020T, manufactured by Negami Chemical Industries, Ltd.) were added at 6.0% by weight, and the mixture was stirred with a stirrer for 1 hour to prepare a composition for forming a surface layer.
[0169] 3-2-2. Application and curing of surface forming composition The pretreated substrate was preheated in a dryer at 60° C. for 30 minutes, and the composition for forming the surface layer was spray-coated using an F-ZERO Type R spray gun (manufactured by Meiji Machinery Works, Ltd.) at an air pressure of 0.2 MPa and a wet weight of 1.0 g. Immediately after coating, the sample was placed in a hot air drying oven and left to stand at 60°C for 10 minutes. Then, an ultraviolet ray irradiation device (MDB15001N-01, manufactured by Sun Energy Co., Ltd.) was used to irradiate the sample with an integrated light dose of 1000 mJ / cm2. 2 (Measured with an ultraviolet integrating light meter, C9536-254, manufactured by Hamamatsu Photonics KK) to cure the coating surface, thereby obtaining a film. In order to remove uncured components, the material was washed with a neutral detergent, rinsed with tap water, and then rinsed with ion-exchanged water. The material was then left to stand at room temperature and dried, to obtain a component sample 1.
[0170] Material sample 2 Member sample 2 was obtained in the same manner as in forming the surface layer of member sample 1, except that a compound having a sulfonic acid group was used instead of the compound having a betaine structure.
[0171] Material sample 3 The component sample 3 was prepared in the following manner.
[0172] 3-3. Formation of the intermediate layer For component sample 3 (compound having a betaine structure+nonionic compound), the intermediate layer was formed in the following manner.
[0173] 3-3-1. Preparation of composition for forming intermediate layer A polymerization initiator was added at a weight concentration of 0.6% and acrylic resin particles (Art Pearl SE-020T, manufactured by Negami Chemical Industrial Co., Ltd.) at a weight concentration of 6.0% to a solution of multifunctional acrylate:solvent = 33:67 (weight ratio), and the mixture was stirred with a stirrer for 1 hour to prepare a composition for forming an intermediate layer.
[0174] 3-3-2. Coating and curing of intermediate layer forming composition The pretreated substrate was preheated in a dryer at 60° C. for 30 minutes, and spray-coated with the composition for forming an intermediate layer of Example 2. An F-ZERO Type R spray gun (manufactured by Meiji Machinery Works, Ltd.) was used, and the coating was performed at an air pressure of 0.2 MPa so that the wet weight was 1.0 g. Immediately after coating, the sample was placed in a hot air drying oven and left to stand at 60°C for 10 minutes. Then, an ultraviolet ray irradiation device (MDB15001N-01, manufactured by Sun Energy Co., Ltd.) was used to irradiate the sample with an integrated light dose of 1000 mJ / cm2. 2 The coating surface was irradiated with ultraviolet light so as to cure the coating (measured with an ultraviolet integrating actinometer, C9536-254, manufactured by Hamamatsu Photonics KK), thereby obtaining an intermediate layer film.
[0175] 3-4. Formation of surface layer For component sample 3 (compound having a betaine structure+nonionic compound), a surface layer was formed in the following manner.
[0176] 3-4-1. Preparation of the composition for forming the surface layer The compound having a betaine structure was dissolved in a solvent so that the weight concentration was 5% and the nonionic compound was dissolved in a solvent so that the weight concentration was 5%. A polymerization initiator was then added to the solution at a weight concentration of 0.2%, and the mixture was stirred with a stirrer for 1 hour to prepare a composition for forming a surface layer.
[0177] 3-4-2. Application and curing of the composition for forming the surface layer The intermediate layer film-forming body was preheated in a dryer at 60°C for 10 minutes, and the surface layer-forming composition prepared in 3-4-1 was spray-coated. The spray gun used was F-ZERO TypeR (manufactured by Meiji Machinery Co., Ltd.), and it was applied at an air pressure of 0.2 MPa to achieve a Wet weight of 3.0 g. Immediately after coating, it was placed in a hot air drying furnace and left standing at 60°C for 10 minutes. Then, using an ultraviolet irradiation device (MDB15001N-01, manufactured by Sun Energy Co., Ltd.), the coated surface was irradiated with ultraviolet light to cure it so that the integrated light quantity was 3 J / cm 2 (measured with an ultraviolet integrated light quantity meter, C9536-254, manufactured by Hamamatsu Photonics K.K.) to obtain a film-forming body. To remove uncured components, after washing with a neutral detergent, rinsing with tap water, further rinsing with ion-exchanged water, and leaving it standing at room temperature to dry, member sample 3 was obtained.
[0178] 4. Evaluation and Results 4-1.XPS evaluation <Preparation of Evaluation Samples> A region with a size of approximately 1 cm square was cut from the plate-shaped member sample and used as a measurement sample. Before measurement, the surface of the measurement sample was washed to thoroughly remove dirt adhering to the surface. Specifically, it was slid and washed with a sponge using a neutral detergent, then ultrasonically washed in ultrapure water at room temperature for 10 minutes, and then thoroughly rinsed with ultrapure water.
[0179] <XPS Measurement> ·XPS Measurement Device K-alpha (manufactured by ThermoFisher Scientific Inc.) was used. ·XPS Measurement Conditions X-ray Conditions: Monochromatized AlKα ray, 72W - 12KV Photoelectron Extraction Angle: 90° Analysis Region: 400μmφ Neutralization Gun Conditions: 200μA Ion Gun Conditions: 10mA (Survey) Time per step: 10ms Energy step size: 1.000eV Sweep: 2 times Pass energy: 200 eV Scanning range: -10~1350 eV (Narrow) Time per step: 50 ms Energy step size: 0.100 eV Sweep: 5 times Pass energy: 50 eV Scanning range: C1s peak 279.000 eV~298.000 eV, O1s peak 525.000 eV~545.000 eV, N1s peak 392.000 eV~410.000 eV, S2p peak 157.000 eV~175.000 eV, Si2p peak 95.000 eV~110.000 eV, P2p peak 124.000 eV~144.000 eV
[0180] <Calculation of atomic concentrations of each atom (S, N)> The atomic concentrations of the detected elements were calculated from the obtained spectra using the data analysis software Thermo Avantage (version 5.9916, manufactured by Thermo Fisher Scientific Co., Ltd.). First, using the spectra obtained from the survey analysis, it was confirmed whether the cleaning was properly performed. Next, for the spectra obtained from the narrow analysis, the charge correction was performed with the C1s peak set at 284.5 eV. Then, after removing the background by the Smart method for the peaks based on the electron orbits of each measured atom, the peak area intensity was calculated, and an analysis process of dividing by the sensitivity coefficient specific to the device preset in the data analysis software was performed to calculate the atomic concentrations when the total of C atoms, O atoms, N atoms, S atoms, and P atoms was 100%.
[0181] <Peak separation of N atoms> To separate the peak derived from the +1-valent N atom (N + ) contained in the betaine structure from the peak derived from the other 0-valent N atom (N 0 ), the following method was used. The peak position of N + was fixed at 401.4~401.8 eV, and the full width at half maximum of the peak was fixed at 1.6 eV. For N0 The peak position of N was fixed at 398.7 to 399.4 eV and peak fitting was performed. + , N 0 The atomic concentration of each was calculated.
[0182] The S atom concentrations and N+ atom concentrations of component samples 1 to 3 are shown in Table X.
[0183] In addition, the analysis depth by XPS is about 10 nm, but in the manufacturing method of the component samples of the examples and comparative examples, a sufficient amount of composition is applied and cured to form a layer thickness of 10 nm, and the layer thickness is sufficiently thicker than the analysis depth by XPS. Therefore, the analysis by XPS can analyze the surface components of the surface layer without being affected by the substrate. In addition, the coated surface can be covered by the application of the bar coat, and the substrate is not exposed. As described above, the analysis by XPS can analyze the surface components of the surface layer without being affected by the substrate.
[0184] <Sliding durability evaluation> A sliding durability test was conducted on component samples 1 and 3 using a sliding machine (manufactured by Tester Sangyo Co., Ltd.). A commercially available urethane sponge (Scotch-Brite Bath Shine, manufactured by 3M Japan Co., Ltd.) was soaked in a mixture of water and neutral detergent (Bath Magiclean, manufactured by Kao Corporation) in a weight ratio of 90:10, and was run back and forth over the surface of the sample 5,000 times with a load of 25 g / cm2. The sample was washed with running water, dried, and the surface after sliding was subjected to XPS measurement using the method described above. The sliding durability was evaluated according to the following criteria. ○:N on the surface after sliding + The concentration of N atoms, S atoms, and P atoms on the surface before sliding + The concentration of the atoms, the concentration of the S atoms, and the concentration of the P atoms are 60% or more. ×: N on the surface after sliding + The concentration of N atoms, S atoms, and P atoms on the surface before sliding + The concentration of the atoms, the concentration of the S atoms, and the concentration of the P atoms are less than 60%.
[0185] The results of the sliding durability evaluation of component samples 1 and 3 are shown in Table 1.
[0186] 4-2.GCIB-XPS evaluation <Preparation of Evaluation Samples> A region with a size of approximately 1 cm square was cut from the plate-shaped component sample and used as the measurement sample. Before measurement, the surface of the measurement sample was cleaned to thoroughly remove the dirt adhering to the surface. Specifically, it was slid and cleaned with a sponge using a neutral detergent, then ultrasonically cleaned in ultrapure water at room temperature for 10 minutes, and then thoroughly rinsed with ultrapure water. ·XPS Measurement Device QUANTERA II (manufactured by ULVAC-PHI, Inc.) was used as the XPS measurement device. ·XPS Measurement Conditions X-ray Conditions: Monochromatic AlKα ray, 25W - 15KV Photoelectron Extraction Angle: 45° Analysis Region: 100μmφ Neutralization Gun Conditions: Auto Neutralizer Ion Gun Conditions: Auto Neutralizer (Narrow) Time per step: 50ms Energy step size: 0.100eV Sweep: 5 times Pass energy: 55eV Scanning Range: C1s peak 279.000eV - 299.000eV, O1s peak 25.000eV - 545.000eV, N1s peak 392.000eV - 410.000eV, S2p peak 157.000eV - 177.000eV, P2p peak 124.000eV - 144.000eV ·GCIB Sputtering Conditions The following conditions were used for GCIB sputtering. Beam Voltage: 10kV Beam Current: 30nA
[0187] <Calculation of Atomic Concentration of Si> The atomic concentrations of the detected elements were calculated from the obtained spectra using the data analysis software MultiPaK (Version 9.0, ULVAC-PHI, Inc.). The obtained spectra were charge-corrected with the C1s peak at 284.5 eV. After that, the background was removed by the Shirley method for the peaks based on the electron orbitals of each measured atom, and the peak area intensity was calculated. The data analysis software was then divided by the device-specific sensitivity coefficient preset in the data analysis software to calculate the atomic concentration of Si when the sum of C, O, N, S, Si, and P atoms was taken as 100%.
[0188] The sputtering rate was calculated by dividing the actual depth of the sputtered mark on the sample after measurement by the sputtering time. The depth at that point was calculated by integrating the sputtering time and the sputtering rate.
[0189] Table 1 shows the Si atom concentrations at a depth of 1 μm in member samples 1 to 3. 4-3.Contact angle The static contact angle of water with respect to the surface of the surface layer was measured under the following measurement conditions using the following device and software. The results are shown in Table 1. Equipment: DMo-702 (Kyowa Interface Science Co., Ltd.) Software: FAMAS integrated interface measurement / analysis system Version:7.3.0 Measurement method: Droplet method Droplet volume: 2.0μL Waiting time: 1000ms Analysis method: θ / 2 method
[0190] 4-4. Evaluation of bacterial stain suppression in the bathroom 4-4-1. Bathroom contamination test (1 month) Each component sample was cut to 7cm x 7cm and placed on the bathroom floor, and a contamination test was conducted for one month under the following conditions. Bathing conditions: After 4 adults bathe in one day Reformed water discharge conditions: With modified water: Hypochlorous acid water is sprayed over the entire floor after cleaning with tap water (using TOTO Ltd.'s Floor Wiper (registered trademark) and operating in normal mode) No modified water: Wash off remaining foam on the surface with a shower Cleaning conditions: No cleaning
[0191] 4-4-2.ATP level measurement The ATP value was measured as an indicator of biological dirt on the surface of each sample one month after the bathroom contamination test using the following method. In the present invention, the "ATP value" refers to the amount of luminescence proportional to the total amount of ATP and AMP using an enzyme cycling method that combines a luminescent reaction by luciferase with pyruvate orthophosphate dikinase, and it can be determined that the lower this value is, the more microbial proliferation is suppressed. ATP levels were measured using an ATP wipe test system manufactured by Kikkoman Corporation under the following conditions. After the bathroom contamination test, a 3.0 cm x 3.0 cm area of each sample's surface was wiped with the company's "Lucipac (registered trademark) Pen," and after reaction with the ATP reaction reagent built into the Lucipac Pen, the amount of luminescence measured using the company's "Lumitester (registered trademark) PD-30" was converted into an ATP value per unit surface area. The results are shown in Table 2.
[0192] [Table 1]
[0193] [Table 2] [Explanation of symbols]
[0194] 1 Water conveyance section 2. Reformed water generator 3. Reformed water discharge section 4, 10 Components 1' Electrolytic section 2' electrolytic cell 3' Control section 21 Inlet 22 Waterway 231 electrode, 2311 anode, 2312 cathode 24 Outlet 11 Base material 12 Surface layer 13. Middle Class 14 Primer layer
Claims
1. a mechanism for discharging reformed water obtained by reforming tap water; a member having a surface onto which the modified water is applied; A facility comprising: The member has a surface, in part or in whole, containing the following formula (A1): 【Chemistry 1】 The surface layer has a sliding durability and includes a structure represented by the formula: In formula (A1), L 1 is -COO-, -CONH-, -(CH 2 ) m - (where m is a natural number), R 1 is H or CH 3 and X 1 is a functional group represented by the following formula (B1) or the following formula (B2), 【Chemistry 2】 【Chemistry 3】 In formula (B1), R 3 and R 6 Each independently represents -(CH 2 ) l - (l is a natural number from 1 to 10), R 4 and R 5 each independently represents a group containing C and H as essential components and O as an optional component, but not containing N or S, In formula (B2), R 7 and R 8 Each independently represents -(CH 2 ) l - (l is a natural number from 1 to 10), R 9 , R 10 , R 11 are each independently a group containing C and H as essential components and O as an optional component, and not containing N or S. The facility is characterized by:
2. The surface of the surface layer is measured by X-ray photoelectron spectroscopy (XPS). N + The concentration of N atoms belonging to is 0.3% or more and 2.8% or less, The concentration of S atoms, the concentration of P atoms, or the sum of the concentration of S atoms and the concentration of P atoms is 0.3% or more, and The concentration of Si atoms is 1.0% or less, 2. The equipment according to claim 1, wherein a concentration of Si atoms obtained by measuring a region from the surface of the surface layer to a point at a depth of 1 μm by X-ray photoelectron spectroscopy (XPS) is 1.0% or less.
3. The equipment according to claim 2 , wherein the static contact angle of water with respect to the surface of the surface layer is 35° or less.
4. The facility according to any one of claims 1 to 3, wherein the modified water is sterilized water or deionized water.
5. The facility according to claim 4, wherein the modified water is electrolyzed water.
6. The facility according to claim 5 , wherein the mechanism comprises a discharge unit that discharges the reformed water, and a device that generates electrolytic water.
Citation Information
Patent Citations
Method for preventing dirt of bathroom and device therefor
JP1997220273A
Composition for forming hydrophilic membrane and hydrophilic member
JP2008239949A
Bathroom
JP2019092841A
Hydrophilic resin composition and laminated sheet
WO2018079592A1
Hydrophilic structure and production method for hydrophilic structure
WO2018155577A1